2022
DOI: 10.3390/antibiotics11091204
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of In Vitro Susceptibility and Resistance Mechanisms in Skin Pathogens: Perspectives for Fluoroquinolone Therapy in Canine Pyoderma

Abstract: Fluoroquinolones (FQ) are commonly used in dogs with bacterial skin infections. Their use as first choice, along with the increased incidence of FQ-resistance, represents a risk to animal and public health. Our study determined minimum inhibitory (MIC) and bactericidal (MBC) concentrations of five FQs in Staphylococcus aureus, Staphylococcus pseudintermedius, and Escherichia coli, together with FQ-resistance mechanisms. MICs, efflux pump (EP) overexpression and MBCs were measured in 249 skin infection isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 82 publications
1
6
0
3
Order By: Relevance
“…These data suggest that fluoroquinolone resistance in S. pseudintermedius is mainly due to target mutations of QRDR region of grlA / gyrA as described by Loiacono and colleagues [ 61 ]. The QRDR mutations herein reported have been already associated with fluoroquinolone resistance in S. pseudintermedius [ 43 , 44 , 62 , 63 ], and are known to convey high MIC CIP values, similar to the ones found in this work [ 41 , 63 , 64 ]. This fact prevented the assessment of a potential effect of EIs upon MIC CIP values.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These data suggest that fluoroquinolone resistance in S. pseudintermedius is mainly due to target mutations of QRDR region of grlA / gyrA as described by Loiacono and colleagues [ 61 ]. The QRDR mutations herein reported have been already associated with fluoroquinolone resistance in S. pseudintermedius [ 43 , 44 , 62 , 63 ], and are known to convey high MIC CIP values, similar to the ones found in this work [ 41 , 63 , 64 ]. This fact prevented the assessment of a potential effect of EIs upon MIC CIP values.…”
Section: Discussionsupporting
confidence: 80%
“…The EIs TZ and VER revealed a mild effect upon MIC CIP values for the TPP NWT strains, resulting mostly in two-fold MIC reductions ( Table 2 ). However, the EIs effect may be masked by the presence of the double mutation S80I (GrlA)/S84L (GyrA) carried by most of these strains, which are often associated with MIC CIP > 32 mg/L [ 43 , 44 ]. The same mild effect of EIs was observed for most TPP WT strains, with only four strains showing a 4-fold MIC CIP reduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, research was focused on investigating the incidence and molecular characterization of extended-spectrum β-lactamase producing Enterobacterales (ESBL-PE) in dogs [ 10 ], with the findings that healthy dogs may be colonized with ESBL-PE multidrug-resistant (MDR) strains, as well as humans, which may serve as a possible source for AMR. Additionally, contemporary perspectives for fluoroquinolone therapy in canine pyoderma and predisposition and resistance mechanisms in skin pathogens were investigated [ 11 ], with findings of fluoroquinolone resistance associated with methicillin-resistant staphylococci. Therefore, Azzariti et al [ 11 ] recommended that fluoroquinolone use should be prudently guided by susceptibility testing.…”
mentioning
confidence: 99%
“…Additionally, contemporary perspectives for fluoroquinolone therapy in canine pyoderma and predisposition and resistance mechanisms in skin pathogens were investigated [ 11 ], with findings of fluoroquinolone resistance associated with methicillin-resistant staphylococci. Therefore, Azzariti et al [ 11 ] recommended that fluoroquinolone use should be prudently guided by susceptibility testing. Debergh et al [ 12 ] have reported the very first finding of MDR Klebsiella pneumoniae of sequence type 11 carrying bla SCO-1 and bla DHA-1 isolated from a four-month-old dog in Belgium.…”
mentioning
confidence: 99%